Pemetaan Tren Riset dalam Manajemen Pendidikan: Studi Bibliometrik dengan VOSviewer (2019-2023) - Mulyanto, Agus; Wardani, Dani; P. Yogaswara, Sunsun; Rukhaida, Ida (UMSU, 2024)
Many researchers, including academics and practitioners, have conducted studies on the topic of educational management. From the many research results on the theme of education management, there needs to be mapping to make it easier for other researchers to see the distribution of research results on education management. It is crucial to map the results of research on education management so that what has been researched can be known and duplication in research can be avoided. This study aims to see research trends related to education management in the Scopus database. The approach in this study uses quantitative (statistical) with the Bibliometric Analysis method. Bibliometric analysis is divided into four stages, namely first determining the purpose and scope of the study, second using science mapping analysis techniques related to education management, collecting data taken from the Scopus database by entering the keyword